GFc7 as a Smart Growth Nanofactor for ex vivo Expansion and Cryoprotection of Humans’ Hematopoietic Stem Cells - Hafizi M (International Journal of Nanomedicine, 2020)
Maryam Hafizi,1 Somayeh Kalanaky,1 Saideh Fakharzadeh,1 Ehsan Janzamin,2 Tarlan Arjmandi,1 Amir Atashi,3,* Mohammad Hassan Nazaran1,* 1Department of Research and Development, Sodour Ahrar Shargh Company, Tehran, Iran; 2Flowcyt Science-Based Company, Tehran, Iran; 3Stem Cell and Tissue Engineering Research Center, Shahroud University of Medical Sciences, Shahroud, Iran*These authors contributed equally to this workCorrespondence: Amir Atashi; Mohammad Hassan Nazaran Tel/Fax +98 23 3239 45000; +98 21 8899 2123Email atashia@shmu.ac.ir; mnazaran@nanochelatingtechnology.comBackground: Nowadays, smart synthesized nanostructures have attracted wide attention in the field of stem cell nanotechnology due to their effect on different properties of stem cells.Methods: GFc7 growth nanofactor was synthesized based on nanochelating technology as an iron-containing copper chelator nanocomplex. The effect of this nanocomplex on the expansion and differentiation of hematopoietic stem cells (HSCs) as well as its performance as a cryoprotectant was evaluated in the present study.Results: The results showed that the absolute count of CD34+ and CD34+CD38− cells on days 4, 7, 10 and 13; the percentage of lactate dehydrogenase enzyme on the same days and CD34+CXCR4 population on day 10 were significantly increased when they were treated with GFc7 growth nanofactor in a fetal bovine serum (FBS)-free medium. This medium also led to delayed differentiation in HSCs. One noticeable result was that CD34+CD38− cells cultured in an FBS medium were immediately differentiated into CD34+CD38+ cells, while CD34+CD38− cells treated with GFc7 growth nanofactor in FBS medium did not show such an immediate significant differentiation. De-freezing GFc7-treated CD34+ cells, which were already frozen according to cord blood bank protocols, showed a higher percentage of cell viability and a larger number of colonies according to colony-forming cell assay as compared to control.Conclusion: It can be claimed that treating HSCs with GFc7 growth nanofactor leads to quality and quantity improvement of HSCs, both in terms of expansion in vitro and freezing and de-freezing processes.Keywords: expansion, GFc7, human hematopoietic stem cells, nanocomplex, nanochelating technology